Developing a research strategy for suicide prevention in the Department of Defense : status of current research, prioritizing areas of need, and recommendations for moving forward - Ramchand, Rajeev (RAND, 2015)
To support U.S. Department of Defense (DoD) efforts to create a unified, comprehensive strategic plan for suicide prevention research, a RAND study cataloged studies funded by DoD and other entities, examined whether current research maps to DoD's strategic research needs, and provided recommendations to encourage better alignment and narrow the research-practice gap when it comes to disseminating findings to programs serving military personnel.